(3QSGdI aj CeQ GdfaS hGdeYGOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3CWGd Gddg HbGA GdTjN GdaGVd dYd SGFd eG bdJg ai GdLhGH GdChd JCedkG HGdESJbUGA ade CSJbd HPdc hJCedJ eG GdSHH GdPi YQV dg s
(3BNQgG (B:s
(3Ch jYOe HYO GdhLhO aEf gPG HGdeYfi GdChd jefY ajg HYV GdGTjGA Cf jchf EPG hLOJ jecf Cf ef PGJgG hdjS cd eG djS hLhOg ef PGJg jLhR Cf jRhd hLhOg hgh GdPi djS cd ajg GdJQcjH GdePchQ hGdMeO dhGgH GdYbd JeJ GdQSGdI s
(3HYK HgG GHf SjfG Edi JdejPg CHj YHjO GdLhRLGfis
(3cJH GdYfhGf HGdGMeQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs